2021
DOI: 10.1177/10783903211058786
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Psychosocial Illness Impact Among Black/African American and Hispanic Older Women Living With HIV

Abstract: Background: In 2018, one in six newly diagnosed individuals with HIV in the United States were adults aged 50 years and older, 24% were women, and 60% were Black/African American and Hispanic (42% and 18%, respectively). Objectives: This study aims to examine the factors associated with HIV psychosocial illness impact among Black/African American and Hispanic older women living with HIV. Method: Guided by the socioecological model, a secondary data analysis design with cross-sectional data that included 138 Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Based on our literature review, we hypothesized that (1) sociodemographic factors associated with multidimensional frailty in the study group include advanced age, lower income, lower educational level, female gender, living without a partner, length of time living with HIV, and a higher comorbidity burden (Falutz, 2020;Iriarte et al, 2021a;Iriarte et al, 2022;Piggott et al, 2016) and (2) psychosocial factors associated with multidimensional frailty include a higher level of HIVrelated stigma, depressive symptoms, greater loneliness, lower perceived social support, and lower acculturation (Falutz, 2020;Iriarte et al, 2021aIriarte et al, , 2021bIriarte et al, , 2022Piggott et al, 2016). This study should contribute to nursing knowledge and inform evidence-based practice to address multidimensional frailty among older Hispanic PLWH by providing opportunities for nurses to understand frailty with a multidimensional approach to health promotion and disease prevention among this population.…”
Section: Study Purposementioning
confidence: 99%
See 1 more Smart Citation
“…Based on our literature review, we hypothesized that (1) sociodemographic factors associated with multidimensional frailty in the study group include advanced age, lower income, lower educational level, female gender, living without a partner, length of time living with HIV, and a higher comorbidity burden (Falutz, 2020;Iriarte et al, 2021a;Iriarte et al, 2022;Piggott et al, 2016) and (2) psychosocial factors associated with multidimensional frailty include a higher level of HIVrelated stigma, depressive symptoms, greater loneliness, lower perceived social support, and lower acculturation (Falutz, 2020;Iriarte et al, 2021aIriarte et al, , 2021bIriarte et al, , 2022Piggott et al, 2016). This study should contribute to nursing knowledge and inform evidence-based practice to address multidimensional frailty among older Hispanic PLWH by providing opportunities for nurses to understand frailty with a multidimensional approach to health promotion and disease prevention among this population.…”
Section: Study Purposementioning
confidence: 99%
“…These professional relationships with nurses may empower and enable PLWH to obtain psychosocial support services from public and community organizations. Such intervention actions could ultimately reduce the psychosocial impact and economic burden of HIV (Iriarte et al, 2021b).…”
Section: Implications For Practicementioning
confidence: 99%
“…Although the study by Logie et al, 2017a was completed in Ontario and this study in British Columbia, they are representative of different health care systems within Canada. Iriarte et al (2021) identified factors that correlated between mental illness and ACB and Hispanic WWH who are 50 years of age or older. The primary identified mechanism to minimize mental health consequences for this population was to develop coping abilities ( Iriarte et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Iriarte et al (2021) identified factors that correlated between mental illness and ACB and Hispanic WWH who are 50 years of age or older. The primary identified mechanism to minimize mental health consequences for this population was to develop coping abilities ( Iriarte et al, 2021 ). Our study found that social support groups were helpful in improving the experience of intersecting stigmatization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation